Advanced technologies of soil moisture monitoring in precision agriculture: A Review - Xiaomo Zhang; Gary Feng; Xin Sun (Journal of Agriculture and Food Research)
Facing the dual challenges of limited natural resources, particularly water, and increasing demands for food security, the role of precision agriculture has become increasingly critical, especially in resource-constrained environments of developing countries. Since its inception in the mid-1980s, precision agriculture in the United States and Europe has evolved to integrate advanced technologies to optimize resource use and minimize environmental impacts, yet it remains in its nascent stages in major developing countries despite attempts at precision irrigation practices. This paper reviews the evolution of soil moisture monitoring technologies from 2013 to 2024, analyzing their strengths, weaknesses, and accuracy in various soil depths to guide modern practices in water and irrigation management within precision agriculture. Highlighting the shift from traditional methods to innovative on-the-go sensors, including electrical, optical, and radiometric sensors, as well as the deployment of unmanned aerial vehicles (UAVs), satellite remote sensing (RS), and IoT-based systems and wireless sensor networks (WSNs), these technologies provide timely, cost-effective, and detailed soil moisture data, significantly enhancing irrigation precision. Our analysis not only showcases technological advancements but also identifies current research gaps, proposing the integration of these technologies to enhance soil moisture management and support sustainable, high-yield agriculture. The anticipated benefits of this integration include improved soil health, increased crop yields, and more effective utilization of water resources, crucial for the sustainability of agriculture in developing nations. By bridging the research-practice gap, this paper aims to foster the adoption of these technologies in precision agriculture, addressing specific agricultural challenges in water-limited settings.